Late Outcomes of Triple Arthrodesis in Patients with Flat Foot - Turchyn, O.A.; Piatkovskyi, V.M.; Lazarenko, H.M.; Liabakh, A.P. (TERRA ORTHOPAEDICA, 2022)
Summary. Triple arthrodesis (TA) is a final surgical decision in treatment of the acquired flat foot (FF). Objective: to study late outcomes of TA in the acquired FF; to establish factors influencing functional outcome of treatment. Materials and Methods. The study included 51 patients (56 feet) with acquired FF at the age 32 – 77 years (54.7±1.2 years). Vertical and horizontal talometatarsal angles (TMA), as well as calcaneal inclination angle were determined by standing radiographs of the foot. The severity of osteoarthritis of the ankle joint (AJ) was assessed according to the Kellgren-Lawrence classification; range of motion in the AJ was determined according to the 0-pass method. Foot function was assessed by the dynamics of indicators: AOFAS scale (hindfoot and ankle joint), FFI (Italian version), quality of life (Roles and Maudsley scale), and VAS (pain). Establishment of factors influencing the outcome of treatment was performed using regression-correlation and factor analysis. Results. Long-term results were studied in 32 cases. Cases of non-unions were registered at the following levels: talonavicular (2) and calcaneocuboidea (2). The dynamics of skiological indicators was significantly positive (p˂0.05; unpaired t-test). According to the AOFAS scale, 2 excellent, 19 good and 11 satisfactory results of treatment were obtained. Significant influence of pain level (inverse dependence) and range of foot extension (direct dependence) on the result (regression analysis) were determined, as well as significant effect of ankle osteoarthritis on the function of the foot (Fisher’s exact test; 0.002). Conclusions. TA in the treatment of acquired FF is an effective surgery that provides favorable results in cases of severe deformity, degenerative changes in the joints, and contraindications to extra-articular corrective osteotomies.